Quantitative Techniques in Participatory Forest Management - Martínez-Falero, Eugenio; Martín-Fernández, Susana; García-Abril, Antonio (Taylor & Francis, 2014)
Forest management has evolved from a mercantilist view to a multi-functional one that integrates economic, social, and ecological aspects. However, the issue of sustainability is not yet resolved. Quantitative Techniques in Participatory Forest Management brings together global research in three areas of application: inventory of the forest variables that determine the main environmental indices, description and design of new environmental indices, and the application of sustainability indices for regional implementations. All these quantitative techniques create the basis for the development of scientific methodologies of participatory sustainable forest management.